Identifying Environmental and Natural Resource Management Conflict Potential Using Participatory Mapping - Brown, Greg; Kangas, Katja; Juutinen, Artti; Tolvanen, Anne (Routledge, 2017)
Methods have been proposed for identifying land use conflict potential using participatory mapping data and models. In a case study from Finland, we extend conflict mapping research by evaluating the capacity for participatory mapping to identify conflict for land uses that include mining, tourism development, commercial forestry, recreation, and nature protection. We evaluated two conflict models using reference sites where conflict was expected and assessed whether conflict potential was influenced by participant social group (resident, visitor, holiday home owner). The conflict models correctly identified the locations of current and proposed mining projects and major tourism locations (ski areas) in the region, while conflict for commercial forestry and reindeer herding was spatially distributed. Preferences for land use by social group were more similar than different across the study region. Identification of conflict potential using participatory mapping can provide a useful planning diagnostic but would benefit from additional research for validation.
Keywords: conflict analysis; PPGIS; public participation; conflicts; analysis; land use; participation